Academic Excellence à la Française: Between Excellence and Equality - Sursock, Andrée (International Higher Education, 2023)
France launched a funding program in 2010 dedicated to ensuring the emergence of five to 10 French universities at the top of international rankings. This initial goal changed overtime to embrace a larger set of institutions and objectives. This article discusses how the extension of excellence challenged the regulatory role of the State, the capacity of universities to act strategically, the relationship between the State and universities, and the landscape of higher education in France.